Implementing the "Everyone is a Teacher Here" Strategy with Audio-Visual Media to Enhance Arabic Speaking Skills in Fifth-Grade Students - Robiyah Nur (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2024)
This study investigates the effectiveness of integrating the "Everyone is a Teacher Here" (ETH) strategy with audio-visual media to enhance Arabic speaking skills (Maharah Kalam) among fifth-grade students at MIS Mathla’ul Anwar, Padang Cermin. Employing Classroom Action Research (CAR) over two cycles, the study involved 20 students as participants. Data were collected through pre-tests, post-tests, structured observations, interviews, and documentation. The findings revealed significant improvements in students' speaking proficiency, with average scores increasing from 61.5 in the pre-test to 67.85 in Cycle 1 and 76.65 in Cycle 2. The passing rate rose from 25% to 95%, indicating substantial progress in fluency, vocabulary usage, and confidence. Observational data highlighted increased student engagement, collaboration, and active participation, while audio-visual media provided contextual and interactive learning experiences. This research aligns with previous studies demonstrating the benefits of cooperative learning and multimedia in language education but offers a novel contribution by integrating these approaches. By situating the intervention in a rural Indonesian context, the study addresses a critical gap in the literature and provides a scalable model for improving language instruction in under-resourced settings. The findings emphasize the transformative potential of combining innovative pedagogical strategies to create inclusive, engaging, and effective learning environments. Future research should explore its application across diverse linguistic and cultural contexts to generalize its efficacy.